Identification and distribution of COPD phenotypes in clinical practice according to Spanish COPD Guidelines: the FENEPOC study - Calle Rubio M; Casamor R; Miravitlles M (International Journal of COPD, 2017)
Myriam Calle Rubio,1,2 Ricard Casamor,3 Marc Miravitlles4 On behalf of the FENEPOC study group1Pulmonary Department, Hospital Clínico San Carlos, 2Department of Medicine, Faculty of Medicine, University Complutense of Madrid, Research Institute of Hospital Clínico San Carlos (IdISSC), Madrid, 3Medical Department, Novartis Farmaceutica, Barcelona, 4Pneumology Department, University Hospital Vall d’Hebron, CIBER de Enfermedades Respiratorias (CIBERES), Barcelona, SpainBackground: The Spanish Guidelines for COPD (GesEPOC) describe four clinical phenotypes: non-exacerbator (NE), asthma-COPD overlap syndrome (ACO), frequent exacerbator with emphysema (EE), and exacerbator with chronic bronchitis (ECB). The objective of this study was to determine the frequency of COPD phenotypes, their clinical characteristics, and the availability of diagnostic tools to classify COPD phenotypes in clinical practice.Materials and methods: This study was an epidemiological, cross-sectional, and multicentered study. Patients ≥40 years old with a post-bronchodilator forced expiratory volume in 1 s (FEV1)/forced vital capacity ratio of <0.7 and who were smokers or former smokers (with at least 10 pack-years) were included. The availability of diagnostic tools to classify COPD phenotypes was assessed by an ad hoc questionnaire.Results: A total of 647 patients (294 primary care [PC], 353 pulmonology centers) were included. Most patients were male (80.8%), with a mean age (SD) of 68.2 (9.2) years, mean post-bronchodilator FEV1 was 53.2% (18.9%) and they suffered a mean of 2.2 (2.1) exacerbations in the last year. NE was the most frequent phenotype (47.5%) found, followed by ECB (29.1%), EE (17.0%), and ACO (6.5%). Significant differences between the four phenotypes were found regarding age; sex; body mass index; FEV1; body mass index, airflow obstruction, dyspnea, and exercise capacity (BODE)/body mass index, airflow obstruction, dyspnea and exacerbations (BODEx) index; modified Medical Research Council dyspnea scale; respiratory symptoms; comorbidities; hospitalizations; and exacerbations in the last year. Physicians considered that >80% of the diagnostic tools needed to classify COPD phenotypes were available, with the exception of computed tomography (26.9%) and carbon monoxide transfer test (13.5%) in PC, and sputum eosinophilia count in PC and pulmonology centers (40.4% and 49.4%, respectively).Conclusion: In Spanish clinical practice, almost half of the patients with COPD presented with NE phenotype. The prevalence of ACO according to the Spanish consensus definition was very low. In general, physicians indicated that they had the necessary tools for diagnosing COPD phenotypes.Keywords: chronic obstructive pulmonary disease, phenotype, diagnosis, emphysema, chronic bronchitis, ACO